Sistem Pakar Mendeteksi Masalah Mesin Inkmaker Dan Mixer Dengan Forward Chaining - Nurhayati, M. Sinta; Hidayat, Rachmat (Sinkron : Jurnal dan Penelitian Teknik Informatika, 2020)
Industrial growth is characterized by the ability to progress in the field of production both in the type of industry, increasing the quality and volume of production activities. Machine is one of the factors of production which determines the smoothness of a production process. In order for the production process to run efficiently, a certain part of the company that is needed to support the maintenance and repair of the machine is called Maintenance Engineering. PT. Segwerk Ind is a multinational company engaged in printing inks for the packaging industry with imported raw materials such as dyes, varnish. The problem of how to maintain the condition of the machine so that it is always prime when production activities take place, Trouble machines are indeed one of the factors that can make a company go bankrupt, such as the production process is hampered, a long machine down time, so that customers will replace their suppliers because they do not want to risk business they are stunted. Therefore, for the success factor of a company's production process, it is required to have appropriate preventive and corrective maintenance activities as well as the problem of lack of competent human resources, therefore we need tools that can solve these problems. The results displayed by making expert system software show that the ink machine problem solving can be known based on the historical machine so that the downtime faced by PT. Segwerk Ind can be pressed as little as possible against machines in the ink industry such as ink printing machines.